Resident evil. Extinction - Anderson, Paul, 1965-; Bolt, Jeremy; Kulzer, Robert; Mulcahy, Russell, 1953-; Jovovich, Milla; Fehr, Oded, 1970-; Larter, Ali, 1976-; Glen, Iain, 1961-; Ashanti, 1980-; Egan, Christopher, 1984-; Locke, Spencer, 1991-; Marsden, Matthew, 1972-; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2008)
Years after the Raccoon City disaster, Alice is on her own. She is aware that she has become a liability and could endanger those around her and she struggles to survive and bring down the Umbrella Corporation led by the sinister Albert Wesker and head researcher Dr. Isaacs. Meanwhile, traveling through the Nevada Desert and the ruins of Las Vegas, Carlos Olivera, L.J., and new survivors K-Mart, Claire Redfield, and Nurse Betty must fight to survive extinction against hordes of zombies, killer crows and a terrifying creatures created as a result of the deadly T-Virus that has already killed millions
Title from container
Special features: Deleted scenes ; Sneak peek of 'Resident evil : degeneration' ; Filmmaker's commentary with director Russell Mulcahy, writer/producer Paul W.S. Anderson and producer Jeremy Bolt ; Making-of featurettes : Alice vision : preproduction, The big bang : shooting 'Resident evil : extinction, ' Bigger, faster, stronger : the undead evolve, Vegas visual effects : miniatures
Director of photography, David Johnson ; editor, Niven Howie ; music by, Charlie Clouser ; costume designer, Joseph A. Porro ; production designer, Eugenio Caballero ; special effects supervisor, Casey Pritchett ; visual effects supervisors, Dennis Berardi, Evan Jacobs
Milla Jovovich, Oded Fehr, Ali Larter, Iain Glen, Ashanti, Christopher Egan, Spencer Locke, Matthew Marsden, Linden Ashby, Jason O'Mara, Mike Epps, Joe Hursley, John Eric Bentley
MPAA rating: R; for strong horror violence throughout and some nudity CHV rating: 18A; gory scences, extreme violence, disturbing content
DVD, region 1, anamorphic widescreen (2.40:1) presentation; Dolby Digital
Keywords: Extinction (Biology) -- Drama; Zombies -- Nevada -- Las Vegas -- Drama; Virus-vector relationships -- Drama; Extinction (Biology) -- Drama; Zombies -- Nevada -- Las Vegas -- Drama; Virus-vector relationship -- Drama; Zombies -- Nevada -- Las Vegas -- Drama; Horror -- Feature; Horror films; Las Vegas (Nev.) -- Drama; Las Vegas (Nev.) -- Drama; Science fiction films; Horror films; Zombie films; Feature films; Horror films; Science fiction films; Feature films; Horror films; Zombie films; Science fiction films; Films for the hearing impaired; Horror -- Feature; Science fiction -- Feature